Determinants and impact of sustainable land management (SLM) investments: A systems evaluation in the Blue Nile Basin, Ethiopia. (16th June 2017) - Schmidt, Emily; Chinowsky, Paul; Robinson, Sherman; Strzepek, Kenneth
Abstract: Ongoing debate over water management along the Blue Nile and land degradation in Ethiopia emphasizes the need for efficiency gains in agricultural production through sustainable land management (SLM). However, previous SLM studies overlook the tradeoffs involved in maintaining SLM investments over time. We address this limitation by combining a household survey that evaluates the economic impacts of SLM investments and maintenance, with a hydrological model that explores location‐specific infrastructure effects. We then use a multi‐market model to evaluate the impacts of alternative SLM investments on agricultural production, prices, and incomes over time. Analysis suggests SLM investments must be maintained for at least seven years to show significant increases in value of production, and that terraces on moderate and steep slopes are most effective in increasing agricultural yields. However, the benefits of terracing do not outweigh the cost of foregone off‐farm labor opportunities, nor compensate for lower agricultural prices from increased supply. Thus, SLM investments must be paired with other input and infrastructure investments, as well as subsidies for initial labor costs, in order to incentivize adoption and long‐term SLM maintenance.